Influence of intravenous iron therapy on mortality and cardiovascular events of patients on hemodialysis: A meta-analysis - Yan Chen; Dian Zhao; Chong Huang; Yanxia Chen; Weiping Tu; Chengyun Xu (Biomolecules & Biomedicine, 2025)
Intravenous (IV) iron is widely utilized to manage anemia in patients undergoing maintenance hemodialysis; however, its long-term safety remains uncertain. This meta-analysis aimed to evaluate the impact of IV iron on all-cause mortality and major adverse cardiovascular events (MACEs) within this population. We conducted a systematic search of PubMed, Embase, Cochrane Library, Web of Science, Wanfang, and CNKI up to March 2025 for randomized controlled trials (RCTs) that compared IV iron with placebo/usual care, oral iron, or varying doses of IV iron in adult hemodialysis patients. The primary outcomes assessed were all-cause mortality and MACEs. Data were synthesized using a random-effects model, and the quality of evidence was evaluated employing the GRADE approach. A total of fifteen RCTs involving 4,257 patients were included in the analysis. Compared to placebo/usual care, IV iron did not significantly affect all-cause mortality (OR: 1.36; 95% CI: 0.60–3.09) or MACEs (OR: 0.81; 95% CI: 0.43–1.55), with a moderate level of evidence. Furthermore, IV iron demonstrated no significant differences in mortality (OR: 0.58; 95% CI: 0.18–1.90) or MACEs (OR: 2.47; 95% CI: 0.37–16.34) when compared to oral iron, although the quality of evidence in this comparison was very low. High-dose IV iron was associated with a reduced mortality rate compared to low-dose IV iron (OR: 0.81; 95% CI: 0.67–0.97), though this result was influenced by a single large study. In conclusion, IV iron does not appear to increase mortality or MACEs relative to placebo or oral iron. While high-dose IV iron may decrease mortality, the evidence remains limited, indicating a need for further research.